The Effect of Job Stisfaction and Job Motivation on Madrasah Ibtidaiyah Negeri Teachers Performance - Nazara, Lily Indra Wirana; Arsyad, Junaidi; Nahar, Syamsu (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
The purpose of this study is to determine the effect of job satisfaction on the performance of state Islamic elementary school teachers in Gunung Sitoli City, the effect of work motivation on the performance of state Islamic elementary school teachers in Gunung Sitoli City, and the effect of job satisfaction and work motivation combined on the performance of teachers of public secondary schools throughout Gunung Sitoli. In this study, the population consisted of 42 permanent teachers who worked at State Islamic Madrasahs throughout Gunung Sitoli. A total sampling technique was used to select the samples. Product Moment Correlation, Simple Regression, and Multiple Regression techniques were used to analyze the data. The study's findings show that water has a significant effect on job satisfaction and performance of Madrasah Ibtidaiyah State Teachers in Gunung Sitoli City, implying that the better the teachers' job satisfaction, the better the teachers' performance, with the magnitude of the effect reaching 14.36 percent. There is a significant and significant effect of work motivation on the performance of State Madrasah Ibtidaiyah teachers in Gunung Sitoli City, which means that the higher the teacher job satisfaction, the higher the teacher performance, with the magnitude of the effect reaching 16.5 percent, and there is a significant effect of job satisfaction and work motivation together on the performance of Madrasah Ibtidaiyah Negeri teachers in Gunung Sitoli City.